Penerapan Model Discovery Learning Pada Materi Gelombang Elektromagnetik Berdasarkan Adsorpsi Congo Red oleh Silika Pasir dengan Metode Spektroskopi - Yuliafitri, Sasti; Swistoro, Eko (UNIB Press, 2024)
This study intended to 1) explain the process of synthesis silica from Bengkulu beach sand; 2) describe pH, weight, contact time, optimum temperature, thermodynamics, isotherms, kinetics of the Congo Red and Remazol Red adsorption process of silica from Bengkulu beach sand using spectroscopic UV-Vis analysis methods. Based on the experiments, the results were 1) The synthesis of silica from Bengkulu beach sand was carried out through the purification of the sample, the potassium silicate preparation (K2SiO3) by the alkali fussion method, gel making, and the silica gel preparation (SiO2). The optimum adsorption condition of Congo Red substance by silica occurs at pH 2 and the contact time is 40 minutes, while the Remazol Red substance occurs at pH 3 and the contact time is 60 minutes, each adsorbent weight 75 mg and 50 mg, and the optimum temperature 30°C. The thermodynamic parameters acquired are ∆G° and ∆H° are negative, while the ∆S° is positive, which means that the process of adsorption occurs exothermic and spontaneously irregularities towards the increased system. Isotherm adsorption is determined through the Freundlich isotherm model and follows pseudo-order kinetic model 2.